Prospective association between dietary pesticide exposure profiles and Type 2 Diabetes risk. (20th October 2021) - Rebouillat, P; Vidal, R; Taupier-Letage, B; Debrauwer, L; Gamet-Payrastre, L; Touvier, M; Fézeu, LK; Lairon, D; Baudry, J; Kesse-Guyot, E
Abstract: Background: Many modifiable risk factors have been identified for type 2 diabetes. However, emerging risk factors such as food contaminants could also play a role and studies are lacking on the subject. We aimed to assess the prospective associations between dietary pesticide exposure profiles and Type 2 Diabetes (T2D) risk among NutriNet-Santé cohort participants. Methods: In 2014, participants completed a Food Frequency Questionnaire, assessing conventional and organic food consumption. Exposures to 25 active substances were estimated using a residue database accounting for farming practices from Chemisches und Veterinäruntersuchungsamt Stuttgart, Germany. Exposure profiles were established using Non-Negative Matrix Factorization (NMF), adapted for sparse data. Cox models adjusted for confounding factors were used to estimate hazard ratios (HR) and 95% confidence interval (95% CI), for the association between the four obtained NMF components and T2D risk. Results: The sample comprised 33, 013 participants aged 53 years old on average, among which 76% of women. During follow-up (median: 5.95 years), 340 incident T2D cases were diagnosed. Positive associations were detected between NMF component 1 (reflecting high exposure to azoxystrobin, chlorpyriphos, imazalil, malathion, profenofos, thiabendazole) and T2D risk: HRQ5 vs Q1=1.47, 95% CI(1.00, 2.18). NMF Component 3 (reflecting low exposure to several synthetic pesticides) was associated with a decrease in T2D risk, among those with high dietary quality only (high adherence to French dietary guidelines): HRQ5vsQ1=0.31, 95%CI(0.10, 0.94). No associations were found for NMF Components 2 and 4. Conclusions: These associations between some pesticide mixtures and T2D diabetes risk need to be confirmed in other types of studies and settings. These results could have important implications for developing prevention strategies, through regulations or dietary guidelines. Key messages: Specific pesticide mixtures could play a role in increased type 2 Diabetes risk. Organic eaters were less exposed to most synthetic pesticides.